The Effect Of Workload And Work Stress On Employee Turnover Intention At PT Sindo Bintangmas Energi - Muhammad Roky Prasetya; Ida Ayu Made E G; Zoniarti Zoniarti (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to analyze the effect of workload and work stress on employee turnover intention at PT. Sindo Bintangmas Energi. The research employs a quantitative approach with an associative method. The population in this study consists of all 45 employees of PT. Sindo Bintangmas Energi, who were also used as the research sample through a saturated sampling technique. Data were collected through questionnaires, while data analysis was carried out using SPSS version 26 with validity tests, reliability tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The results of the multiple linear regression analysis produced the equation: Y = 2.672 + 0.657X1 + 0.022X2 + 1.245. The findings indicate that the workload variable has a positive and significant effect on turnover intention , with a t-value of 6.801 > t-table value of 2.018 and a significance level of 0.000 < 0.05. Conversely, work stress has no significant effect on turnover intention , with a t-value of 0.202 < t-table value of 2.018 and a significance level of 0.841 > 0.05. The simultaneous test (F-test) shows that workload and work stress jointly have a significant effect on turnover intention , with an F-value of 187.160 > F-table value of 3.22 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) is 0.899, indicating that 89.9% of the variation in turnover intention can be explained by the two independent variables, while the remaining 10.1% is explained by other factors outside this study.